Orchestrated desaturation reprogramming from stearoyl‐CoA desaturase to fatty acid desaturase 2 in cancer epithelial‐mesenchymal transition and metastasis - Zhicong Chen; Yanqing Gong; Fukai Chen; Hyeon Jeong Lee; Jinqin Qian; Jing Zhao; Wenpeng Zhang; Yamin Li; Yihui Zhou; Qiaobing Xu; Yu Xia; Liqun Zhou; et al. (Cancer Communications)
Abstract Background Adaptative desaturation in fatty acid (FA) is an emerging hallmark of cancer metabolic plasticity. Desaturases such as stearoyl‐CoA desaturase (SCD) and fatty acid desaturase 2 (FADS2) have been implicated in multiple cancers, and their dominant and compensatory effects have recently been highlighted. However, how tumors initiate and sustain their self‐sufficient FA desaturation to maintain phenotypic transition remains elusive. This study aimed to explore the molecular orchestration of SCD and FADS2 and their specific reprogramming mechanisms in response to cancer progression. Methods The potential interactions between SCD and FADS2 were explored by bioinformatics analyses across multiple cancer cohorts, which guided subsequent functional and mechanistic investigations. The expression levels of desaturases were investigated with online datasets and validated in both cancer tissues and cell lines. Specific desaturation activities were characterized through various isomer‐resolved lipidomics methods and sensitivity assays using desaturase inhibitors. In‐situ lipid profiling was conducted using multiplex stimulated Raman scattering imaging. Functional assays were performed both in vitro and in vivo, with RNA‐sequencing employed for the mechanism verification. Results After integration of the RNA‐protein‐metabolite levels, the data revealed that a reprogramming from SCD‐dependent to FADS2‐dependent desaturation was linked to cancer epithelial‐mesenchymal transition (EMT) and progression in both patients and cell lines. FADS2 overexpression and SCD suppression concurrently maintained EMT plasticity. A FADS2/β‐catenin self‐reinforcing feedback loop facilitated the degree of lipid unsaturation, membrane fluidity, metastatic potential and EMT signaling. Moreover, SCD inhibition triggered a lethal apoptosis but boosted survival plasticity by inducing EMT and enhancing FA uptake via adenosine monophosphate‐activated protein kinase activation. Notably, this desaturation reprogramming increased transforming growth factor‐β2, effectively sustaining aggressive phenotypes and metabolic plasticity during EMT. Conclusions These findings revealed a metabolic reprogramming from SCD‐dependent to FADS2‐dependent desaturation during cancer EMT and progression, which concurrently supports EMT plasticity. Targeting desaturation reprogramming represents a potential vulnerability for cancer metabolic therapy.